SELECTIVE PERFUSION OF ABDOMINAL ORGANS DURING SURGERY FOR THORACOABDOMINAL ANEURYSM OR JUXTA-RENAL ABDOMINAL ANEURYSM - SHIMOJI, M.; SHIMABUKURO, M.; KOJA, K.; MIYAGI, K.; UEZU, T.; KUSABA, A.; AKASAKI, M.; KAMIZATO, T.; KUDAKA, M.; KUNIYOSHI, Y. (Jinko Zoki, 1997)
During the last 2 years, we treated eight cases of thoracoabdominal aneurysm and two cases of juxta-renal abdominal aneurysm with selective perfusion of abdominal organs. The serum BUN, Cr, GOT, GPT and total bilirubin up to 4weeks after operation were compared to those of the non-perfusion cases as controls (n=8). These parameters of, the patients receiving perfusion tended to normalize earlier than those of the control group. We concluded that selective perfusion to the major abdominal arterial branches by our method is effective in preserving the function of the abdominal organs.